Knowledge of Islamic Jurisprudence among Secondary School Students in Kuwait - Haya M. Alalanda; Bader M. Alansari (Sultan Qaboos University, 2016)
This study aimed to examine the interaction effect between gender and stream in high school (scientific vs. literary) on the Islamic jurisprudence knowledge. The study used a sample of 1371 individuals (623 males, 784 females) from grade 12 of public secondary schools in Kuwait. Participants responded to an Islamic jurisprudence knowledge scale. The result revealed no significant differences between males and females in the total score and the percentage rate of the students who passed the Islamic jurisprudence knowledge scale. Moreover, a significant difference was found between students in the scientific and literary streams on the total score and the percentage of the passing students in the Islamic jurisprudence knowledge scale favoring the scientific section students. Also, there was no significant interaction effect between gender and high school stream on Islamic jurisprudence knowledge sale.